75ce8c92e0919e76e3ba80c7e7e53616eeefd3f7
[ginac.git] / doc / powerlaws.tex
1 \documentclass{article}
2
3 \begin{document}
4
5 \section{Power Laws}
6
7 \subsection{Definitions}
8
9 Definitions for power and log:
10 \begin{equation}
11 x^a \equiv e^{a \ln x}
12 \end{equation}
13 \begin{equation}
14 \ln x \equiv \ln |x| + i \arg(x) \mbox{ where } -\pi < \arg(x) \le \pi
15 \end{equation}
16
17 \subsection{General rules}
18
19 \begin{equation}
20 e^x e^y = e^{x+y}
21 \end{equation}
22 for arbitrary complex $x$ and $y$
23
24 \begin{equation}
25 x^{-a} = \frac{1}{x^a}
26 \end{equation}
27 for arbitrary complex $x$ and $a$
28
29 \subsection{$(ax)^b=a^b x^b$}
30
31 \subsubsection{$b$ integer, $x$ and $a$ arbitrary complex}
32
33 assume $b>0$
34
35 \begin{eqnarray}
36 (ax)^b & = & \underbrace{(ax) \cdots (ax)}_{b \times}
37 \nonumber\\
38 & = & \underbrace{a \cdots a}_{b \times}
39       \underbrace{x \cdots x}_{b \times}
40 \nonumber\\
41 & = & a^b x^b \mbox{ q.e.d.}
42 \end{eqnarray}
43
44 if $b<0$ (so $b=-|b|$)
45 \begin{eqnarray}
46 (ax)^b & = & \frac{1}{(ax)^{|b|}}
47 \nonumber\\
48 & = & \frac{1}{a^{|b|} x^{|b|}}
49 \nonumber\\
50 & = & a^{-|b|} x^{-|b|}
51 \nonumber\\
52 & = & a^b x^b
53 \end{eqnarray}
54
55 \subsubsection{$a>0$, $x$ and $b$ arbitrary complex}
56
57 \begin{eqnarray}
58 (ax)^b & = & e^{b \ln(ax)}
59 \nonumber\\
60 & = & e^{b (\ln |ax| + i \arg(ax))}
61 \end{eqnarray}
62
63 if $a$ is real and positive:
64 \begin{equation}
65 \ln |ax| = \ln |a| + \ln |x| = \ln a + \ln |x|
66 \end{equation}
67 and 
68 \begin{equation}
69 \arg(ax) = \arg(x)
70 \end{equation}
71
72 So
73 \begin{eqnarray}
74 e^{b (\ln |ax| + i \arg(ax))} & = &
75 e^{b (\ln a + \ln |x| + i \arg(x))}
76 \nonumber\\
77 & = & e^{b (\ln a + \ln x)}
78 \nonumber\\
79 & = & e^{b \ln a} e^{b \ln x}
80 \nonumber\\
81 & = & a^b x^b \mbox{ q.e.d.}
82 \end{eqnarray}
83
84 \subsection{$(x^a)^b = x^{ab}$}
85
86 \subsubsection{$b$ integer, $x$ and $a$ arbitrary complex}
87
88 assume $b>0$
89
90 \begin{eqnarray}
91 (x^a)^b & = & \underbrace{(x^a) \cdots (x^a)}_{b \times}
92 \nonumber\\
93 & = & \underbrace{e^{a \ln x} \cdots e^{a \ln x}}_{b \times}
94 \nonumber\\
95 & = & e^{\underbrace{\scriptstyle a \ln x + \dots + a \ln x}_{b \times}}
96 \nonumber\\
97 & = & e^{a b \ln x}
98 \nonumber\\
99 & = & x^{ab} \mbox{ q.e.d.}
100 \end{eqnarray}
101
102 if $b<0$ (so $b=-|b|$)
103 \begin{eqnarray}
104 (x^a)^b & = & \frac{1}{(x^a)^{|b|}}
105 \nonumber\\
106 & = & \frac{1}{x^{a|b|}}
107 \nonumber\\
108 & = & x^{-a|b|}
109 \nonumber\\
110 & = & x^{ab}
111 \end{eqnarray}
112
113 \subsubsection{$-1 < a \le 1$, $x$ and $b$ arbitrary complex}
114
115 We have
116 \begin{equation}
117 x^a=e^{a \ln|x| + ia\arg(x)}
118 \end{equation}
119 if $a$ is real
120 \begin{equation}
121 |x^a|=e^{a\ln|x|}
122 \end{equation}
123 and
124 \begin{equation}
125 \arg(x^a)-a\arg(x)=2k\pi
126 \end{equation}
127 now if $-1 < a \le 1$, then $-\pi < a\arg(x) \le \pi$,
128 and so $k=0$, i.e.
129 \begin{equation}
130 \arg(x^a)=a\arg(x)
131 \end{equation}
132 (Note that for $a=-1$ this may not be true, as $-1 \arg(x)$ may be equal to $-\pi$.)
133 So
134 \begin{eqnarray}
135 \ln(x^a) & = & \ln|x^a| + i\arg(x^a)
136 \nonumber\\
137 & = & \ln (e^{a\ln|x|})+ia\arg(x)
138 \nonumber\\
139 & = & a \ln |x| + ia\arg(x) \mbox{ (because $a\ln|x|$ is real)}
140 \nonumber\\
141 & = & a\ln x
142 \end{eqnarray}
143 Hence
144 \begin{eqnarray}
145 (x^a)^b & = & e^{b\ln x^a}
146 \nonumber\\
147 & = & e^{ba\ln x}
148 \nonumber\\
149 & = & x^{ab} \mbox{ q.e.d.}
150 \end{eqnarray}
151
152 proof contributed by Adam Strzebonski from Wolfram Research
153 ({\tt adams@wolfram.com}) in newsgroup {\tt sci.math.symbolic}.
154
155 \end{document}